A Chromosome-Level Genome Assembly of Dendrobium Huoshanense Using Long Reads and Hi-C Data. (12th October 2020) - Han, Bangxing; Jing, Yi; Dai, Jun; Zheng, Tao; Gu, Fangli; Zhao, Qun; Zhu, Fucheng; Song, Xiangwen; Deng, Hui; Wei, Peipei; Song, Cheng; Liu, Dong; et al.
Abstract: Dendrobium huoshanense is used to treat various diseases in traditional Chinese medicine. Recent studies have identified active components. However, the lack of genomic data limits research on the biosynthesis and application of these therapeutic ingredients. To address this issue, we generated the first chromosome-level genome assembly and annotation of D. huoshanense . We integrated PacBio sequencing data, Illumina paired-end sequencing data, and Hi-C sequencing data to assemble a 1.285 Gb genome, with contig and scaffold N50 lengths of 598 kb and 71.79 Mb, respectively. We annotated 21, 070 protein-coding genes and 0.96 Gb transposable elements, constituting 74.92% of the whole assembly. In addition, we identified 252 genes responsible for polysaccharide biosynthesis by Kyoto Encyclopedia of Genes and Genomes functional annotation. Our data provide a basis for further functional studies, particularly those focused on genes related to glycan biosynthesis and metabolism, and have implications for both conservation and medicine.